Efficiency of carbon dioxide capture in a rotating packed bed with diifferent absorbents - Zabolotnyi, O.; Solomakha , A. (Energy and Automation, 2025)
One of the effective approaches to reducing CO₂ emissions is the use of liquid absorbents in various types of contact devices, particularly in centrifugal rotating packed bed (RPB) absorbers. This study presents a comparative analysis of chemical liquid absorbents (NaOH, MEA, piperazine) based on mass transfer efficiency, thermal and oxidative stability, regeneration energy demand, and economic feasibility. It was found that centrifugal contactors demonstrate a significantly higher volumetric mass transfer coefficient compared to conventional packed absorption columns, especially when using MEA. The influence of absorbent concentration and hydrodynamic parameters on mass transfer intensity was analyzed. The results show that piperazine, despite its higher cost, provides the best operational performance. The research offers a foundation for selecting absorbents considering both technical and economic parameters as well as mass transfer efficiency, aimed at compact and energy-efficient CO₂ capture systems. Key words: liquid absorbents, rotating packed bed, CO2 capture, mass transfer